Implicit black‐weapon associations weakened over time in increasingly multiethnic metropolitan areas. Issue 1 (18th December 2020) - Somo, Angela; Sadler, Melody; Devos, Thierry
Abstract: A repeated cross‐sectional design was used to examine whether temporal changes in implicit Black‐weapon associations were dependent on the changing ethnic diversity of metropolitan areas over the course of a decade (2009–2018). Data on implicit Black‐weapon associations were obtained from Project Implicit. Three indicators of ethnic diversity were calculated using American Community Survey data. Minority representation referred to the proportion of African American residents. Variety was operationalized as the degree to which six ethnic groups each accounted for an equal proportion of the population. Integration assessed the degree to which ethnic groups were evenly distributed across census tracts making up the metropolitan area. Multilevel model analyses ( N = 345, 647 participants, nested within 185 metropolitan areas) revealed that implicit Black‐weapon associations weakened over time, and to a larger degree in metropolitan areas characterized by steeper increases in variety. This longitudinal relationship is consistent with the notion that, as metropolitan areas become more multiethnic, implicit associations between crime, danger, or violence and Black Americans decline.